An Intercultural Approach for Language Teaching: Developing Critical Cultural Awareness - Agudelo, John Jader (Íkala, Revista de Lenguaje y Cultura, 2007)
This article presents the pedagogical experience of a teacher implementing an intercultural approach in an undergraduate foreign language teaching program. The students who participated in this experience were interviewed in order to demonstrate that an intercultural approach is an effective alternative to developing students’ critical cultural awareness, as well as to explore the critical relationship between language and culture. Analysis of the interviews revealed critical cultural awareness in students’ teaching practices and personal views. It also showed students becoming conscious of the essential role of culture in language teaching. How to reference thus article: Agudelo, J. J. (2007). An Intercultural Approach for Language Teaching: Developing Critical Cultural Awareness. Íkala. 12(1), pp. 185 – 217.